Evaluation of Sirtuin 3 level and some biochemical parameters in people with Parkinson's disease - Noor Abdulsatar Majeed; Mohammed Bahry Hassin (African Journal of Advanced Pure and Applied Sciences, 2023)
The study aimed to evaluate the levels of Sirtuin 3 (SIRT3), along with various biochemical parameters, in individuals diagnosed with Parkinson's disease. Additionally, the potential relationship between these parameters and factors such as age, gender, and blood group. The findings of the study indicated significant variations in SIRT3 levels among individuals with Parkinson's disease. Moreover, observed correlations between SIRT3 levels and certain biochemical parameters. These parameters included markers of oxidative stress, inflammation, and neurodegeneration, which are commonly associated with Parkinson's disease. The study was conducted on (50) healthy and Parkinson’s patients, their ages ranged between (30–80) years, and the study indicated that there was a significant decrease in the probability level (P ≤0.05) for the level of SIRT3 in the blood serum of the patients with Parkinson’s disease of both genders. It also aimed to study the impact of oxidative stress on patients with Parkinson’s disease and compare it with the healthy ones, by measuring (17) variables of oxidation and antioxidants. The results showed that there was a significant decrease at the probability level (p≤0.05) in the level of SIRT3 at the probability level (p≤0.05) and a significant increase at the probability level (p≤0.05) in the level of malondialdehyde, glucose, and copper in comparison with healthy people. The results showed a significant decrease in the patients with Parkinson’s disease in all antioxidants (vitamin C - bilirubin - albumin - Ceruloplasmin- glutathione - iron) compared to healthy people because of the increased oxidative stress. As for lipid profile, the results indicate a significant decrease in levels of (TC, TG, HDL-C, LDL-C, and VLDL-C). Also, the results showed a significant decrease in the concentration of (uric acid, zinc, and lipid profile).